Steady State Growth of the Long-Run Sales-Maximizing Firm: Comment - Seoka, Yoshihiko (Quarterly Journal of Economics, 1983)
Steady State Growth of the Long-Run Sales-Maximizing Firm: Comment Get access Yoshihiko Seoka Yoshihiko Seoka Osaka City University, Japan Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 98, Issue 4, November 1983, Pages 713–719, https://doi.org/10.2307/1881786 Published: 01 November 1983